Software engineering economics for the certified software development associate - Towhidnejad, Massood (IEEE, 2012)
This tutorial is part of a series of eLearning courses designed to help you prepare for the examination to become a Certified Software Development Associate (CSDA) or to learn more about specific software engineering topics. Courses in this series address one or more of the fifteen Knowledge Areas that comprise the Software Engineering Body of Knowledge - or SWEBOK, upon which the Certification Exam is based. This course is intended to assess your understanding of software requirements through inline quizzes and feedback. The CSDA credential is intended for graduating software engineers and entry-level software professionals and serves to bridge the gap between your educational experience and real-world work requirements. Software Engineering Economics reviews technical decision-making with the business goals of the organization in mind. In this tutorial you will review basic concepts including the Minimum Acceptable Rate of Return (MARR), future and present value, and net present value. Additional content areas include taxes, for and not-for-profit decision making, software project estimation, risk management, techniques for estimating uncertainty and multiple attribute decisions